54‐3: Reduced Solar‐Loading Using Micro‐Mirror Array in Automotive HUD. Issue 1 (28th June 2022) - Li, Kenneth
Abstract : Automotive head‐up displays (HUDs) use windshields as part of the display system and are used as partial reflectors for reflecting the images formed inside the dash board towards the driver. The locations of the aerial images are usually at the bumper of the vehicle and beyond, depending on the requirements. One of the major issues with such HUD system is the solar loading created by sunlight shining into the system through the image forming optics with focusing properties especially when the sun is shining into the HUD system in an off‐axis manner. This paper describes a HUD system where the imaging system uses a Micro‐Mirror Array Plate (MMAP) with an optical design that eliminates the issues associated with the off‐axis sunlight. Solar loading is an important design criterion as the HUD optics concentrate the sunlight to levels that can damage the display panel. Based on the aerial imaging properties of MMAP, this design would be applicable to the use of Dihedral Corner Reflector Array (DCRA), and Aerial Imaging by Retro‐Reflection (AIRR). Bench‐top system has been set up using MMAP from ASKA3D, Japan with the expected imaging properties. A complete prototype is being fabricated and will be reported.